2010
DOI: 10.1152/ajpendo.00534.2009
|View full text |Cite
|
Sign up to set email alerts
|

LATS1 phosphorylates forkhead L2 and regulates its transcriptional activity

Abstract: is expressed in the ovary and acts as a transcriptional repressor of the steroidogenic acute regulatory (StAR) gene, a marker of granulosa cell differentiation. Human FOXL2 mutations that produce truncated proteins lacking the COOH terminus result in blepharophimosis/ptosis/epicanthus inversus (BPES) syndrome type I, which is associated with premature ovarian failure (POF). In this study, we investigated whether FOXL2's activity as a transcriptional repressor is regulated by phosphorylation. We found that FOXL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 61 publications
3
28
0
1
Order By: Relevance
“…Although Chen et al confirmed that YAP1 appears to be a new susceptibility gene for PCOS in Han Chinese women [49], we cannot exclude more localized changes in Hippo genes expression at the cellular level. Furthermore, LATS1 phosphorylated forkhead L2 (FOXL2) and regulated its transcriptional activity in some ovary of primary ovarian insufficient POI patients [50,51]. In this study, our results also confirmed that the Hippo signal pathway relates with the maturation of mammalian oocytes, proliferation of granulosa cells and follicular atresia in folliculogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…Although Chen et al confirmed that YAP1 appears to be a new susceptibility gene for PCOS in Han Chinese women [49], we cannot exclude more localized changes in Hippo genes expression at the cellular level. Furthermore, LATS1 phosphorylated forkhead L2 (FOXL2) and regulated its transcriptional activity in some ovary of primary ovarian insufficient POI patients [50,51]. In this study, our results also confirmed that the Hippo signal pathway relates with the maturation of mammalian oocytes, proliferation of granulosa cells and follicular atresia in folliculogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…Some of these signals could include changes in cell-cell contact, cell density, or cell-extracellular matrix (ECM) interactions [39][40][41]. The Hippo pathway could also interact with well-known regulators of follicular development, such as FOXL2 [42] and members of the TGF-beta family, through interaction with SMAD signaling proteins [43][44][45]. Hippo signaling could also be regulated by secreted paracrine or endocrine factors that act through G-protein coupled receptors: Studies using multiple mammalian cell lines suggest that GPCR-mediated diffusible signals can either up-regulate or down-regulate the activity of YAP1/WWTR1 by acting through Rho GTPase and actin cytoskeleton [46][47][48].…”
Section: Hippo Signaling In the Ovarymentioning
confidence: 99%
“…This differential activity is likely dependent on specific FOXL2 binding partners that constitute the transcriptional complex leading to gene regulation (Fleming et al, 2010; Pisarska et al, 2010, 2011; Georges et al, 2013) as well as post-translational modifications (PTMs) and variant alternative FOXL2 binding sites (see below). A variety of protein binding partners of FOXL2 have been reported, including DEAD box-containing protein (DP103; Lee et al, 2005), SMAD3 (Blount et al, 2009), ER alpha, (Kim et al, 2009), Steroidogenic factor-1 (SF-1; Park et al, 2010), UBC9, PIAS1 (Marongiu et al, 2010), LATS1 (Pisarska et al, 2010), FOXL2 itself (Kuo et al, 2011), CXXC4, CXXC5, CREM, GMEB1, NR2C1, SP100, RPLP1, BANF1, XRCC6, SIRT1 L’HĂ´te et al, 2012), GSK3β, MDM2 (Kim et al, 2014) and NOBOX (Bouilly et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…As PTMs, sumoylation, phosphorylation and acetylation, have all been shown to modulate FOXL2 activity (Kuo et al, 2009; Marongiu et al, 2010; Pisarska et al, 2010; Georges et al, 2011; Kim et al, 2014). Recent evidence indicates that such modifications can even drive FOX factors to bind to particular target genes in response to environmental signals (Benayoun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%